Current and future perspectives for Helicobacter pylori treatment and management: From antibiotics to probiotics - Liang, Bing; Yuan, Yang; Peng, Xiao-Jin; Liu, Xin-Lin; Hu, Xiao-Kun; Xing, Dong-Ming (Frontiers in Cellular and Infection Microbiology, 2022)
Helicobacter pylori (H. pylori) is a common human pathogen that infects roughly half of the world's population and causes gastrointestinal diseases such as chronic gastritis, dyspepsia, and peptic ulcers, as well as being an important cause of gastric cancer. In developing countries, H. pylori infection is responsible for approximately 63% of gastric cancer cases. With the increased antibiotic resistance of H. pylori, the effectiveness of conventional antibiotic eradication therapy is diminishing. Recent studies have shown that specific probiotic strains may improve the efficacy of H. pylori eradication therapy. In this review, we compare main consensus guideline points and summarize the current antibiotic treatments for H. pylori and the combination of probiotic-assisted treatment strategies. In particular, we highlight the existing scientific evidence of Limosilactobacillus reuteri (L. reuteri), an important member of the probiotics family, for H. pylori treatment and discuss its clinical research application from an evidence-based standpoint, with the goal of providing new ideas for the fight against H. pylori and more options for those infected.